Estimasi dan Validasi Total Digestible Nutrient Hijauan Pakan dari Komposisi Kimia Pakan - D M Sinaga; A Jayanegara; E B Laconi (PETERPAN (Jurnal Peternakan Terapan), 2023)
This study aims to estimate and validate the accuracy of estimated Total Digestible Nutrient (TDN) content in forages based on the chemical composition of feed. Data on nutrient composition for estimates were obtained from the BR-CORTE database consisting of 86 types of forages and primary data from observations consisting of 19 types of forages. Analysis data is used Pearson correlation, multiple linear regression, determination coefficient (R2), and root mean square error (RMSE) for estimation models, variance test (ANOVA), and T-test for validation. The results showed that forage TDN had a negative correlation with Neutral Detergent Fibre (NDF) (P <0.01) and lignin (P <0.05), but was positively correlated with Non-Fibre Carbohydrate (NFC) (P <0.01), Ether Extract (EE) and Crude Protein (CP) (P<0.01). Thus, the TDN value can be estimated from the chemical composition in the feed. The regression equation that will be used to estimate forage TDN content is TDN = 0.482 NDF + 1.538 EE + 0.699 NFC + 0.718 CP (R2=0.994). Then, this equation is validated and compared to the Hartadi’s and Wardeh’s equations. The results of the T-test showed that the TDN value estimated is non significantly different with TDN Hartadi for cattle (P>0.05). It concluded TDN value of local forage can be estimated based on this estimation models.